Understanding Bankruptcy: The Interplay of Financial Attitude, Knowledge, Investment Choices, and Behavior - Christophorus Indra Wahyu Putra (Dinasti International Journal of Management Science, 2024)
The purpose of this article is to know the importance of financial literacy, financial education, and financial behavior in the context of individual financial decisions. It provides a solid theoretical foundation for the analysis of the relationship between bankruptcy and factors such as financial attitudes, financial knowledge, and misconduct in finance. This article uses a qualitative method which provides a literacy of articles related to the topic in this article from reputable international journals or international journals with databases in accordance with the English Nation. Literature comes from the last ten years, by providing a view and proposal for further research with the modern concept above. The offering of the model in this study provides an opportunity for other researchers to use as a reference, also the literature above in supporting this article is limited to dozens of articles that according to the researcher have a connection, where bankruptcy often results from a combination of negative financial attitudes, inadequate financial knowledge, wrong investment decisions, and poor financial behavior. Addressing these factors requires a holistic approach that includes financial education, promoting responsible financial attitudes and behaviors, and providing support for individuals to make informed financial decisions. By empowering individuals with the necessary knowledge and skills to manage their finances effectively, the risk of bankruptcy can be mitigated, leading to greater financial stability and well-being.